Outside-In and Inside-Out Perspectives: An Analysis of ESG’s Social Dimension in Indonesian Air Navigation Company - Erlyansa Cahyandari; Marko Sebira Hermawan (Institute of Research and Community Outreach - Petra Christian University, 2025)
The increasing quality issues of sustainability reports in general include several important aspects that can affect the credibility and usefulness of the report. In this context, the materiality of information enhances the relevance and transparency of the company's disclosures. This study examines the implementation of social materiality perspectives at the Indonesian Air Navigation Company within the Environmental, Social, and Governance (ESG) principles framework by integrating the outside-in and inside-out perspectives. Utilizing a materiality perspective, this research supports organizations in preparing disclosures of essential information within sustainability reports. The research uses a qualitative method, utilizing document review and semi-structured interviews with key stakeholders to explore ways to disclose outside-in and inside-out perspectives with sustainability reporting. The findings show that integrating social components into a company's ESG framework highlights its approach to materiality. The company measures its operational activities against various external requirements, embodying an outside-in perspective that reflects how external factors affect its operations. The company's materiality is in line with the outside-in perspective that takes into account investor considerations and financial risks; this also shows the use of the POJK 51 / POJK.03 / 2017 framework to adjust to the company's needs. Meanwhile, the company continues to allocate resources for social initiatives that improve stakeholder welfare, which represents an inside-out materiality perspective where internal capabilities are utilized to overcome operational pressures.